The founding of the University of Belgrade and the controversy over the Faculty of Theology 1905-1920 - Lolić Marinko (Filozofija i Društvo, 2007)
The paper presents and sheds light on a 1919 controversy unfolding in the periodical Demokratija. Its main protagonists were the notable Serbian philosopher Branislav Petronijević, theologist Radovan Kazimirović and physiologist Ivan Đaja, and it concerned the proposal to establish a Faculty of Theology in Belgrade. The debate reflects in fact the conflict among Serbian intellectuals over fundamental principles of the university. We believe this is a most important intellectual dispute taking place in our academic public in the early 20th century. Although historical records indicate that the position of the Faculty of Theology within the future University was discussed as early as the 19th century, when the first ideas of founding a University in Serbia had been put forward, with discussions culminating on the occasion of the establishment of the first Serbian University in 1905, the questions raised then remained mainly unsolved and marked the one-century of the Belgrade University, the most prestigious Serbian institution of higher learning. Turbulent changes in our society in the 1990s announced new searches and radical reevaluation of the condition of our higher education. The problem of the Faculty of Theology thus resurfaced within not just academic but also broader political and cultural public. Unfortunately, some participants in this debate, disregarding the complexity of the issue, have focused their attention on the communist period alone, when the Faculty of Theology was separated from the University. In this way they avoid facing the crucial problem of the contemporary Serbian society - the problem of building modern secular educational and political institutions. .